O fluido etéreo nos estudos do conde Rumford sobre a propagação do calor - Alves, Eliade Amanda (2018)
The aim of this work is to comprehend at which moment and for which reasons count Rumford went on to admit the existence of an ethereal fluid to support his hypothesis about media of heat propagation. Thus, we analyzed a series of experiments performed between 1786 and 1804 elaborated by him to investigate about the modes of heat communication. A carefully examination of these experiments and arguments presented by Rumford shows us that the process of the elaboration of his hypothesis was gradual and that took into account not only experimental questions, but also theoretical ones. Through this analysis, we concluded that Rumford took almost twenty years to admit the existence of an ethereal fluid and to present the definite version of his hypothesis that the heat was propagated through undulations in ether